Knowledge, attitude, and practices of recycling and its associated factors among undergraduate students in Universiti Putra Malaysia, Serdang - Nordin, F. N.; Muhamad Saliluddin, Suhainizam (Community Health Society Malaysia, 2016)
Background: Urbanisation, industrialisation processes, and human activities are one of the causes of the increasing amount of solid waste production which leads to a myriad of problems to the environment as well as cause diseases due to improper solid waste disposal and increasing amount of solid wastes in landfills. Being a ‘green’ university, Universiti Putra Malaysia Serdang (UPM) has had held various activities and provided facilities to promote recycling behaviour among their students. Conservation behaviour of a group of young adults is pertinent as they will grow and mature to become future leaders responsible for environmental stewardship and sustainability. Hence this study will focus on undergraduate students in UPM Serdang, as university students embody various expression of characteristics in comparison to the general population. Materials and Methods: This is an analytical cross-sectional study, conducted on 310 undergraduate students in UPM, Serdang from three randomly selected faculties. Proportionate stratified random sampling was used to determine the sample size from each faculty. Self-administered questionnaires were used. Data analyses were conducted using SPSS version 22, and p-value <0.05 is considered significant. Results: This study reported to have high levels of knowledge, negative attitude and poor practice on recycling among the respondents. Significant associations present between faculty of study, previous recycling practices and previous recycling campaign involvement to the level of recycling knowledge as well as with level of recycling practices. Previous recycling practices and the Faculty of Medicine and Health Sciences are the predictors for high level of knowledge. While previous recycling practices, Faculty of Human Ecology, and having high level of knowledge are the predictors for good practices. Conclusion: Recycling attitude is lacking, which exhibits lack of environmental awareness among respondents. There is a need for behavioural and attitudinal change in respect for environmental sustainability by improving the level of recycling practice.